PERKEMBANGAN KONSUMSI DAN PENYEDIAAN ENERGI DALAM PEREKONOMIAN INDONESIA - Elinur '; D S Priyarsono; Mangara Tambunan; Muhammad Firdaus (Indonesian Journal of Agricultural Economics, 2010)
Indonesia is one country that is extravagant in energy utilization. On the otherhand the energy supply is relatively stagnant and even showed a declining trend,particularly in fuel oil supply. Therefore very interesting to discuss about thedevelopment of energy consumption based on the users and the energy supply by typeof energy. Trend analysis is used to show the pattern in energy supply by type of energyand energy consumption according to the user, combined with a descriptive analysis todescribe the problems and advantages of the fluctuations that occur from the results oftrend analysis are presented.The results show that the energy consumption across all sectors, namelyindustrial sector, household sector, transport sector, agriculture and other sectors, tendsto increase. Meanwhile, the overall energy supply tends to increase, but with a smallerincrease than the increase of consumption. This results in Indonesia is highly dependenton imports, especially imports of fuel oil.In order to solve the energy problem in Indonesia is needed for energyconservation, namely by making energy savings campaign, the establishment of energyconservation laws, and establishment of energy conservation center. Besides, it alsorequired a low interest rate policy and a stable exchange rate to encourage investment inenergy sector for increased crude oil production and counteract the negative impact ofrising world oil prices which led to decrease of energy supply. In the long term need toattempt to shift the use of energy sourced from unrenewable resources to the use ofenergy that are renewable resources, such as utilization of water energy, wind, biomass,biodiesel, biogas and sustainable energy sources other. In other words needed greenenergy strategy.